Peningkatan Kompetensi Otomasi Mesin Industri menggunakan Human Machine Interface (HMI) untuk Guru Vokasi - Sardi, Juli; Habibullah, Habibullah; Eliza, Fivia; Risfendra, Risfendra; Hendra, Ayu; Setyawan, Herlin (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
The enhancement of teachers' competencies in industrial automation technology is urgently needed to address the challenges of Industry 4.0. This study aims to measure the effectiveness of the training program Industrial Machine Automation Using Human Machine Interface (HMI) in improving teachers' competencies at SMK Negeri 5 Solok Selatan. The research employed a One Group Pre-test Post-test Design method, with data analysis conducted using the Paired Sample T-Test. A total of 20 teachers participated in the training, which consisted of theoretical sessions, software simulations, and hands-on practice with HMI hardware. The results indicated a significant improvement in participants' competencies, with the average score increasing from 55 in the pre-test to 83.25 in the post-test (p<0.05). The training effectively strengthened participants' conceptual understanding, programming skills, and troubleshooting abilities. Furthermore, the program was deemed relevant to the technological needs of vocational education, supporting the integration of automation technology into the vocational school curriculum. This study concludes that HMI training can serve as a strategic model for teacher competency development, contributing to improving vocational education quality. Recommendations include conducting advanced training sessions, enhancing collaboration with industry, and developing project-based curricula oriented toward modern technologies.